Virtual Multiple Skill Laboratory: An Integrated Web-Based Experiment for Science Students - Malik*, Adam; Chusni, Muhammad Minan; Ubaidillah, Mujib; Zakwandi, Rizki; Nugraha, Andi Rohendi (Universitas Syiah Kuala, 2025)
The 21st-century skills are essential for students to adapt to global changes in economics, ecosystems, and politics by developing critical thinking, communication, collaboration, adaptability, and creativity. This article discusses the development of a practicum learning website using the virtual multiple skill laboratory model (VMSLM), an innovation made in response to the obstacles faced in implementing the VMSLM during the covid-19 pandemic. Although focused on solutions during the pandemic, the results of this development have broader potential in supporting online-based practicum learning and distance learning in the future. This research is developmental research that prioritizes qualitative testing as the primary data source. However, quantitative analysis is also required to provide support for the qualitative findings. The results showed that the website developed was considered good and feasible to use based on the results of group discussions with experts. A positive response was also given by the experienced group, who stated that the VMSLM website provided a comprehensive learning experience. These results indicate that practicum using the VMSLM website has the potential to be a valuable tool in the development of physics learning in the future. In addition to providing practical solutions during the pandemic, the use of VMSLM can also support changes towards more interactive, effective, and inclusive learning. Thus, the development of VMSLM websites not only provides a short-term solution but also offers a sustainable contribution to the overall transformation of physics learning